Proposals for the Second Five Year Plan Harijan and Tribal Welfare Department Vol. No. I Government of Madhya Bharat - Planning Commission (Planning Commission, 1955)
At the initial stage of the First Five Year Plan Welfare activities only for the Scheduled Tribes and the Scheduled Castes were envisaged. Subsequently in the year 1953-54 the Ex-Criminal Tribes were brought under the preview of the Welfare Schemes, while Other Backward Classes ( Bhils & Bhilalas ) were Included in the ameliorative programme only in the year 1954-55.
Government of Madhya Bharat